Exploitnig DNS Server Vulnerabilites Using Linux Operating System - Abdulrahman, Aysar A.; Jumaa, Alaa K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Today, the world is using many modern Information Technology (IT) systems to gather, store, and manipulate important information. On the other hand, hackers are trying to gain access to any computer or system for viewing, copying, or creating data without the intention of destroying data or maliciously harming the computer. Exploiting domain name system (DNS) vulnerabilities have resulted in a range of high profile disruptions and outages for major internet sites around the world. DNS attack is an exploit in which an attacker takes advantage of vulnerabilities is the (DNS). This paper will present the vulnerabilities and the weak points of the DNS server and how attackers (black hat hakcer) can exploit those vulnerabilities to attack and gain access to the server machine. In conclusion, presenting and implementing this project make users understand the hazard of hackers. Then, will lead to build secure and protected systems and applications.